Short Communication: Response of insect foragers to four soybean mutant lines cultivated in savanna agro-ecology of Ghana (Asian Journal of Agriculture, 2020)
Abstract. Philip AA, Adu-Acheampong S, Addai IK. 2020. Short Communication: Response of insect foragers to four soybean mutant lines cultivated in savanna agroecology of Ghana. Asian J Agric 5: 1-3. To increase soybean production, different lines have been developed with improved qualities to withstand problems associated with the production process. However, such development can render the lines (e.g., mutant lines) susceptible to pest attacks. We sampled for insect abundance and diversity within four soybean lines (150Gy, 200Gy, 250Gy, 300Gy) cultivated under two levels of NPK-15-15-15 fertilizer to check if mutagenesis has increased their attraction to insect activities including pest attacks. Some of the species recorded were Acanthacris ruficornis, Apis mellifera, Spodoptera frugiperda, Helicoverpa armigera, Bemisia tabaci, and Callosobruchus spp. The study also realized that NPK-15-15-15 had no significant impact on insects recorded within the various mutant lines. This only translates into no special pest attraction due to mutagenesis of not for any line. We recommend from this study that farmers should not have any reservation for cultivating any recommended mutant line for mass production after all other tests are completed on them before release.
Keywords: Fertilizer, foragers, insect, lines, mutagenesis, soybean